INTELLECTUAL CAPITAL AND FINANCIAL PERFORMANCE ON BANKING FIRMS IN INDONESIA - Tang, Sukiantono (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
With the rapid advancement of global economic progress, lot of innovation has been made and attract researchers to investigate Intellectual Capital (IC). The purpose of this paper is to find any relationship Intellectual Capital toward Financial Performance. Using Value Added Intellectual Coefficient (VAIC) Model and the modified version as the research model. This study takes secondary data from companies that published its annual financial statement in Indonesia Stock Exchange during 2017 until 2022. The gathered data then analysed by using regression panel method. This research shows that Human capital doesn’t significantly affect ROA and ROE but does significantly affect ATO in both VAIC model and Modified VAIC model. Structural capital also insignificantly affects ROE and ROE but significantly affect ATO when tested using VAIC model. Capital employed and innovation capital is proven to a positive significant effect to all dependent variables.